1987
DOI: 10.1007/bf00635365
|View full text |Cite
|
Sign up to set email alerts
|

A 7-week follow-up study of the behaviour of testosterone and cortisol during the competition period in rowers

Abstract: Nine rowers (six men of the regional and three women of the national top class) participated in the study. During 7 consecutive weeks of the competition period serum testosterone (T), SHBG, cortisol (C) and urea were determined at the same time every morning under fasting conditions. From the concentrations of T and SHBG the free testosterone fraction (T/SHBG) was calculated, and from the concentrations of T and C the ratio of T/C was derived. The object of the investigation was to gather information on a pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
2
11

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(52 citation statements)
references
References 23 publications
3
36
2
11
Order By: Relevance
“…Furthermore, basal serum cortisol decreased with a concomitant increase in the number of subjects who felt overloaded. Previously, serum total testosterone concentration has been shown to decrease in response to demanding training periods (6,37), as well as during extremely stressful military training periods (25,26), and to increase with overload training (36). In contrast to the present study, basal SHBG has been found to increase (19,23) and IGF-1 to decrease (23-26) after heavy training.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, basal serum cortisol decreased with a concomitant increase in the number of subjects who felt overloaded. Previously, serum total testosterone concentration has been shown to decrease in response to demanding training periods (6,37), as well as during extremely stressful military training periods (25,26), and to increase with overload training (36). In contrast to the present study, basal SHBG has been found to increase (19,23) and IGF-1 to decrease (23-26) after heavy training.…”
Section: Discussioncontrasting
confidence: 92%
“…In addition, IGF-1 is sensitive to both energy intake and dietary protein content, and demonstrates significant decreases with inadequate dietary intake (23,24). Furthermore, a 7 week intensive endurance overload training program (36) and combined endurance and strength overload training for 6 weeks (5) have been found to decrease testosterone/cortisol ratios. Even the biochemical changes of testosterone and testosterone/cortisol ratio are controversial compared to previous findings, a stagnation of increase in VO 2 max in this study indicates that the training load during the second half of the 8-week training period may have been too exhaustive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28] It has also been suggested that T:C is an indicator of anabolic-catabolic balance. 29,30 Despite testosterone, cortisol, and T:C being several of the most common biochemical markers used in training studies in an attempt to monitor an athlete's response to training stimuli, the literature offers mixed conclusions about whether these are viable markers of an athlete's training status. For instance, testosterone, cortisol and T:C ratio in endurance athletes have not shown to respond consistently to increased or decreased training load or when overreached and overtrained.…”
Section: Introductionmentioning
confidence: 99%
“…T/C ratio [3,7,29]. T/C ratio has been suggested as a potential marker for insufficient recovery and overtraining syndrome in athletes as it was decreased after intensive endurance exercise [19] and chronic high volumes of endurance training [28,29]. Our research has shown that the level of T/C ratio decreases significantly from preparatory phase to the competitive phase in the female swimmers.…”
Section: Resultsmentioning
confidence: 53%